2016
DOI: 10.1186/s40510-016-0129-x
|View full text |Cite
|
Sign up to set email alerts
|

Displacement and force distribution of splinted and tilted mandibular anterior teeth under occlusal loads: an in silico 3D finite element analysis

Abstract: BackgroundFixed orthodontic retainers have numerous advantages, but it is not known whether they can exert pathological forces on supporting tissues around the splinted teeth. The purpose of this study was to investigate how the inclination of the lower anterior teeth can affect dental displacement and also change the direction of occlusal loads exerted to dental and its supporting tissues.MethodsFour three-dimensional finite element models of the anterior part of the mandible were designed. All the models con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…The equivalent stresses in proclined teeth were concentrated palatally around the CEJ, and were 80% greater in dentine than in the properly positioned teeth. Similar results have been achieved by a study conducted by Gerami et al, 8 which showed that increasing the labial angle of the mandibular central incisors resulted in much higher cervical stresses in splinted and tilted teeth under occlusal loads. This situation may produce a cervical tooth fracture.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The equivalent stresses in proclined teeth were concentrated palatally around the CEJ, and were 80% greater in dentine than in the properly positioned teeth. Similar results have been achieved by a study conducted by Gerami et al, 8 which showed that increasing the labial angle of the mandibular central incisors resulted in much higher cervical stresses in splinted and tilted teeth under occlusal loads. This situation may produce a cervical tooth fracture.…”
Section: Discussionsupporting
confidence: 89%
“…Occlusal loading of substantially proclined anterior teeth can have a traumatic effect on the surrounding tissues. 8 Higher inclination of anterior teeth results in higher stress in the tooth, Results. The lowest reduced stresses were recorded for the palatally inclined incisors (model A1).…”
Section: Introductionmentioning
confidence: 99%
“…In another finite element study, they had stated that there was a correlation between different inclinations of tooth to the rate of displacement and the von Mises stress generated in the PDL. 17 The reason for the maximum displacement in the premolars as compared with the lateral incisors in our models for the given clinical situation could be because root of the first premolar was comparatively short than the laterals and had only a single root instead of two roots, i.e., one buccal and one palatal. Added to that, the long axis of the first premolar and the lateral incisor to the occlusal plane differed.…”
Section: Discussionmentioning
confidence: 99%
“…This difference in the displacement may be due to the variations in the tooth size, morphology, the alveolar bone height, or even the teeth inclinations. 16,17 Tanne et al, 16 in their FEA study, had stated that root length and alveolar bone height affect the pattern of initial tooth displacements both in the center of resistance and the centers of rotation. In another finite element study, they had stated that there was a correlation between different inclinations of tooth to the rate of displacement and the von Mises stress generated in the PDL.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, FEM has been used for models with a single tooth [7][8][9], partial jawbone models with several teeth [10][11][12], and complete jawbone models with all teeth [13][14][15][16]. Additionally, these finite-element models have been used to explore the effects of the design and material properties of different orthodontic forces, brackets, and archwires on the biomechanical responses of the PDL during tooth movement.…”
Section: Introductionmentioning
confidence: 99%